Adult partner preference and sexual behavior of male rats exposed prenatally to betamethasone - Piffer, Renata C.; Garcia, Patricia C.; Pereira, Oduvaldo C. M. (Pergamon-Elsevier B.V. Ltd, 2009)
The aim of this Study was to investigate long-term effects of prenatal betamethasone exposure oil sexual partner preference, testosterone level, and sexual behavior. Pregnant rats received 0.1 mg/kg of betamethasone or saline on the 12th, 13th, 18th, and 19th days of pregnancy. Parameters in male offspring were evaluated at 90 days of age. Male rats from the betamethasone group did not show any difference in sexual partner preference as expressed by the total number of visits to the female or male zone. However, these males spent significantly less total time and shorter duration per visit in the female zone than their controls. Therefore, prenatal exposure to betamethasone led to a significantly lower sexual female partner preference score compared to the control group. These animals also presented diminished testosterone levels in adulthood. Prenatal exposure to betamethasone induced a delay in the latency to first ejaculation. as well as a decrease in the numbers of postejaculatory intromissions, total intromissions and total ejaculations. Although 80% of the betamethasone-treated animals exhibited male Sexual behavior, when they were castrated and pretreated with estrogen, 50% of them showed lordosis and accepted mounts of another sexually experienced male. These results suggest that the prenatal treatment with betamethasone, by increasing maternal corticosteroid level, may have diminished testosterone peak in male pups, a peak crucial to brain sexual differentiation. As a consequence, the prenatal betamethasone treatment reduced the testosterone level in adulthood and altered partner preference and Sexual behavior. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Prenatal betamethasone; Corticotherapy; Brain sexual differentiation; Sexual partner preference; Sexual behavior; Testosterone; Male rat